2011
DOI: 10.5812/asjsm.34753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fasting During Ramadan Month on Cognitive Function in Muslim Athletes

Abstract: Background: Existing research suggests that irisin increases in response to exercise in humans. However, results are controversial and a majority of the studies lack a control group. The present study aimed to analyze the effects of both one-bout, and three-week intense resistance training on physical fitness (body composition and strength) and serum irisin levels when compared to a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 36 publications
5
86
3
Order By: Relevance
“…This is most likely due to learning effects, which are also documented in other studies (Tian et al 2011, Lotfi et al 2010, Doniger and Simos 2006, Halyburton et al 2007. Halyburton et al (2007) also found a practise effect for the Digit Span Backward test, albeit significantly smaller than the time effect in our study.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…This is most likely due to learning effects, which are also documented in other studies (Tian et al 2011, Lotfi et al 2010, Doniger and Simos 2006, Halyburton et al 2007. Halyburton et al (2007) also found a practise effect for the Digit Span Backward test, albeit significantly smaller than the time effect in our study.…”
Section: Discussionmentioning
confidence: 51%
“…Participants in the study by Tian et al (2011) had better reaction times during the second half of Ramadan (P<0.01) at the identification task of the CogState test (11). Dolu et al (2007) found that concentration of medical students at the Mesulam and Weintraum Cancellation Tasks was lower during the first week Ramadan, with less targets marked and more targets missed (P<0.01) (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sleep disturbances, general fatigue, and impairment of cognitive functions (Kadri et al, 2000;Leiper et al, 2003;Tian et al, 2012). Research related to Ramadan and performance in Malaysia have been helpful in understanding how Ramadan fasting affects sports performance (see Aziz & Weileen, 2008;Roy et al, 2011a;Roy et al, 2011b;Singh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%